2008
DOI: 10.5194/nhess-8-1309-2008
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous ELF phenomena in the Schumann resonance band as observed at Moshiri (Japan) in possible association with an earthquake in Taiwan

Abstract: Abstract. The ELF observation at Moshiri (geographic coordinates: 44.29 • N, 142.21 • E) in Hokkaido, Japan, was used to find anomalous phenomena in the Schumann resonance band, possibly associated with a large earthquake (magnitude of 7.8) in Taiwan on 26 December 2006. The Schumann resonance signal (fundamental (n=1), 8 Hz; 2nd harmonic, 14 Hz, 3rd harmonic, 20 Hz, 4th, 26 Hz etc.) is known to be supported by electromagnetic radiation from the global thunderstorms, and the anomaly in this paper is characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 14 publications
6
25
0
Order By: Relevance
“…This kind of SR anomaly has been then confirmed by a statistical study of observation in Nakatsugawa for EQs with magnitude greater than 5.0 in Taiwan over a period of six years . Hayakawa et al (2008) have further confirmed the presence of similar SR higher mode enhancement at Moshiri, Japan, in possible association with the so-called Ping-tong EQ in Taiwan.…”
Section: Introductionsupporting
confidence: 79%
“…This kind of SR anomaly has been then confirmed by a statistical study of observation in Nakatsugawa for EQs with magnitude greater than 5.0 in Taiwan over a period of six years . Hayakawa et al (2008) have further confirmed the presence of similar SR higher mode enhancement at Moshiri, Japan, in possible association with the so-called Ping-tong EQ in Taiwan.…”
Section: Introductionsupporting
confidence: 79%
“…A correlation between ELF-VLF waves and earthquakes has been addressed by the seismology community. Employing statistical analyses, Hayakawa et al (1993Hayakawa et al ( , 2008 suggest anomalous effects in Schumann resonance spectra might be associated to earthquakes. They also claim that seismic activity modifies the rate and intensity of whistlers.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, ELF-VLF transient response due to earthquakes deserves further investigation. Anomalous effects in Schumann resonance phenomena possibly associated with earthquakes have been claimed (Hayakawa et al, , 2008. Even so, unambiguous causeeffect relation between Schumann resonance and earthquakes is difficult to establish because of the higher natural variability of lightning activity and of the ionosphere.…”
Section: Sources Outside the Cavitymentioning
confidence: 99%
“…Anomalous radio signals in the Schumann resonance (SR) band were reported for the first time in a series of works (Ohta et al 2001(Ohta et al , 2006Hayakawa et al 2005aHayakawa et al , 2008Hayakawa et al , 2010b. Analyses of the long-term SR records indicated that anomalies are usually observed in Japan when earthquakes (EQs) occur in Taiwan.…”
Section: Introductionmentioning
confidence: 99%